ANALISIS PERAN GURU DALAM MENSTIMULASI KEMAMPUAN BAHASA LISAN ANAK USIA 4-5 TAHUN DI TK SWASTA KATOLIK BUDI MURNI 2 MEDAN - Vinni Alvionita Br Karo; Dwi Septi Anjas Wulan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the teacher's role as facilitator and model in stimulating the expressive oral language skills of children aged 4–5 years at TK Swasta Katolik Budi Murni 2 Medan. The study is grounded in the importance of the teacher's role in supporting children's language development through daily learning interactions. A descriptive qualitative approach was employed, with the classroom teacher and fifteen children in group A as research subjects. Data were collected through five days of non-participant observation and semi-structured interviews with the classroom teacher, then analyzed using the Miles and Huberman interactive model comprising data reduction, data display, and conclusion drawing, with technical triangulation applied to ensure the credibility of the findings. The results show that the teacher's facilitator role was realized through the provision of varied, multimodal learning activities, a flexible and supportive learning environment, and diverse instructional media. Meanwhile, the teacher's model role was realized through consistently demonstrating proper and polite Indonesian language use and providing constructive responses to children's speech. Both roles were found to operate in an integrated and complementary manner, proving effective in optimally supporting the development of children's expressive oral language. These findings confirm the relevance of the facilitator-and-model role framework and social learning theory in early childhood language stimulation practice.